A two-stage robust approach for the reliable logistics network design problem - Cheng, Chun; Qi, Mingyao; Zhang, Ying; Rousseau, Louis-Martin (Transportation research. Part B: methodological, 2018)
•Three two-stage robust models for the reliable logistics network design problem.•Performance tests show superiority of the proposed exact algorithm.•System’s reliability can be improved with a slight increase in the normal cost.•The expanded model can better balance cost, risk, and computational time.•The risk-constrained model can be a decision support tool for system expansion. This paper examines a three-echelon logistics network in which all supply and transshipment nodes are subject to disruption. We use uncertainty sets to describe the possible scenarios without depending on probabilistic information. We adopt a two-stage robust optimization approach where location decisions are made before and recourse decisions are made after the disruptions are known. We construct three two-stage robust models, which are solved exactly by a column-and-constraint-generation algorithm. Numerical tests demonstrate that the proposed algorithm outperforms the Benders decomposition method in both solution quality and computational time, and that the system’s reliability can be improved with only a slight increase in the normal cost.